2009
DOI: 10.1080/09670260802428250
|View full text |Cite
|
Sign up to set email alerts
|

Caulerpa racemosa: adaptive varieties studied by fatty acid composition (Northern Adriatic Sea, Vrsar, Croatia)

Abstract: Total lipids and fatty acid composition were monitored seasonally in exposed and sheltered Caulerpa racemosa settlements along the coast of St Juraj island (Vrsar, Croatia). The underlying sediment in the exposed area was characterized by a lower content of total lipids (0.63 AE 0.18 mg/g d.w.) and coarser grain sizes (median particle diameter [Md] ¼ 1319.5 mm) in comparison to sediment of the sheltered area (0.89 AE 0.06 mg/g d.w.; Md 378.9 mm). Despite the proximities of both populations studied, and, hence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Cells were washed with distilled water and stained in 1.0% (w/v) uranyl acetate overnight. Cells were then dehydrated in an upgrade series of ethanol and embedded in Epon 812 (for more details, see Eggert 2002) water temperature in winter (Blažina et al 2009). By this increased low-temperature tolerance, this species can successfully survive the winter without visible necrotic parts or chilling injuries.…”
Section: Disruptive Temperature Stress and Thermal Tolerancementioning
confidence: 99%
“…Cells were washed with distilled water and stained in 1.0% (w/v) uranyl acetate overnight. Cells were then dehydrated in an upgrade series of ethanol and embedded in Epon 812 (for more details, see Eggert 2002) water temperature in winter (Blažina et al 2009). By this increased low-temperature tolerance, this species can successfully survive the winter without visible necrotic parts or chilling injuries.…”
Section: Disruptive Temperature Stress and Thermal Tolerancementioning
confidence: 99%
“…The lipid metabolism of macroalgae is modulated in response to changes in environmental factors such as temperature and light [27,28,29,30,31,32,33,34]. The variation of lipids with season was evaluated in the brown alga Fucus serratus .…”
Section: Introductionmentioning
confidence: 99%
“…Marine algae have been also recognized as potential source of antioxidants [14,15] and traditionally consumed as a readily available whole food, especially among coastal communities [16,17,18]. Fatty acids and enzymatic and non-enzymatic antioxidant properties of have been investigated in Caulerpa species [19,20,21,22]. Macroalgae also contain bioactive substances like polysaccharides, proteins, lipids, and polyphenols, with antibacterial, antiviral, and antifungal properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean, the production of secondary metabolites by the alga changes seasonally and the highest levels have been observed during the period of vegetative algal growth (summer and autumn) [37]. Moreover Blažina et al [20] observed that in C. racemosa from sheltered sites generally small variations in total lipids were found.…”
Section: Introductionmentioning
confidence: 99%